Medication Adherence and Its Associated Factors Among Type II Diabetes Mellitus Patients Presenting to Health Centres in Tirupati, Andhra Pradesh, India - B, Ajeetha; Damu Ade, Anju; Guthi, Visweswara Rao; Meesala, Lalith (National Journal of Community Medicine, 2025)
Background: Diabetes is a swiftly expanding health issue. To avoid or postpone the development of complications, patients need to adherent to their antidiabetic drugs. The objective was to assess medication adherence and to determine the association between medication non-adherence and socio-demographic characteristics, co-morbidities, and self-care and medication practices among Type II Diabetes Mellitus patients. Methods: An analytical cross-sectional study was conducted among 216 diabetic patients of more than 18 years of age with duration at least 6 months presenting to the 4 health centres in Tirupati. Medication adherence was assessed using the nine-item Hill-Bone Medication Adherence Scale (HBMAS). Results: The study found that among the 216 participants, 82.9% were adherent while 17.1% were non-adherent to medications. On multivariate analysis, age group of >60 years (AOR=2.97(95% CI 1.158-7.662), belonging to rural areas (AOR=22.163 (95% CI:2.404-193.678), not following any dietary modifications (AOR= 2.976 (95% CI 0.935-9.479) and dependent on family member for medication intake remembrance (AOR=6.103(0.875-42.546) were found to be more at risk for non-adherence. Conclusions: One-fifth of the study participants were non-adherent to medications. Increasing age, rural population, not following dietary modifications, and dependent on family members to remind them for medication intake were found to be associated with medication non-adherence.